Extended Cyclic Deformation Recovery of the Indentation‐Induced Two‐Way Shape‐Memory Effect in Nickel–Titanium. Issue 4 (18th January 2019) - Laursen, Christopher M.; Anderson, Mitchell P.; Frick, Carl P.
Abstract : The indentation‐induced two‐way shape‐memory effect (TWSME) has appeal for active surface applications due to its simple training procedure and temperature dependent shape‐shifting nature. However, a direct investigation into the repeatability over many cycles and factors that may limit its longevity remain unanswered; even though most proposed applications would rely on long‐term, cyclic loading. Therefore, the explicit purpose of this study is to investigate the influence that indentation temperature and upper cycle temperature have on TWSME behavior over multiple cycles. A 50.3 at% Ni–Ti shape‐memory alloy was Vickers indented to a load of 80 N at various indentation temperatures which span the material's martensitic and austenitic phases. Samples are then thermally cycled from 15 °C below the martensitic finish temperature to a predetermined upper cycle temperature of either 10 °C or 150 °C above the austenitic finish temperature for up to 1000 cycles. Results suggest that the magnitude of the TWSME deformation recovery is governed by indentation temperature and upper cycle temperature much more so than the specific cycle number. Most importantly, as upper cycle temperature increases beyond the austenite finish temperature there is a significant decrease in the TWSME which remains subdued upon a return to reduced upper cycle temperatures in subsequent cycles. Abstract : For the first time, the effect of repeated thermal cycling is explicitly investigated for the indentation‐induced two‐way shape memory (TWSME) effect in nickel–titanium. The results show the TWSME is relatively stable for up to 1000 cycles and likely beyond. However, heating to temperatures well over the austinite finish temperature degrades the TWSME in a single cycle.